2017
DOI: 10.1016/j.biocon.2017.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Divergent responses of sympatric species to livestock encroachment at fine spatiotemporal scales

Abstract: 2017-08-25T16:27:24

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
52
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 69 publications
(57 citation statements)
references
References 46 publications
3
52
0
2
Order By: Relevance
“…In our study, the government encouraged livestock grazing with a cash incentive policy when previous main livelihoods (e.g., nature-based tourism and agricultural production) were blocked by the damaged road. Our results show that although the earthquake did not seriously affect giant panda habitat, livestock expansion has seriously degraded giant panda habitat , Zhang et al 2017. We suggest that the local administration implements policy to control the number and activity range of livestock in the reserve, and ban livestock (e.g., yaks and sheep) from giant panda core habitat.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…In our study, the government encouraged livestock grazing with a cash incentive policy when previous main livelihoods (e.g., nature-based tourism and agricultural production) were blocked by the damaged road. Our results show that although the earthquake did not seriously affect giant panda habitat, livestock expansion has seriously degraded giant panda habitat , Zhang et al 2017. We suggest that the local administration implements policy to control the number and activity range of livestock in the reserve, and ban livestock (e.g., yaks and sheep) from giant panda core habitat.…”
Section: Discussionmentioning
confidence: 86%
“…But pastureland in Wolong is quite limited. Many livestock have begun to graze in the forest, and research has shown that livestock severely degrade bamboo resources and panda habitat , Zhang et al 2017. This is because giant pandas and other threatened wildlife practice direct avoidance strategies.…”
Section: Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…The estimated 1864 remaining giant pandas (State Forestry Administration of the People's Republic of China 2015) are facing many humaninduced threats including road construction, timber harvesting, and livestock grazing (Hull et al 2014;Hong et al 2015Hong et al , 2016Liu 2015;Zhang et al 2017a). Although pandas have a simple digestive tract with no enzymes to digest the cellulose that is found in fibrous bamboo culms (Hu et al 2010;Li et al 2010;Wei et al 2012;Nie et al 2015), they do have adaptations that allow them to subsist on a bamboo diet such as enlarged molars and specialized gut microbes to aid in cellulose digestion (Zhu et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…。2008 年から 2013 年までのカメラトラップ研究論文 266 本をレビュー した総説 (Burton et al, 2015)によれば,2008 年に 26 本だった論文数は 2013 年には 2.6 倍の 67 本にまで増加 した。ほとんど(94.8%)の論文が哺乳類を対象に含ん でいたが,分類群別にみると 64.7%が食肉目,40.2%が 偶蹄類を対象に含む一方で,霊長類を対象に含む論文 は 10.5%に留まっていた (Burton et al, 2015) 。さらに, 全体の 86.8%の論文が何らかの方法で分布や密度の推 定を目的としていた一方で,行動観察を目的としたも のは 32.3%に留まっていた (Burton et al, 2015) Naing et al, 2015;Nakashima, 2015;Norris et al, 2012;Rovero & De Luca, 2007) 。こういった調査はカメラトラップ法だけでなく, トランセクト法や地域住民への聞き取りなど複数の手 法を用いて行われることも多い。また,Vanthomme et al(2013)は哺乳類リスト作成から一歩踏み込んで, 各哺乳類種の地域的な在・不在が様々な人為的攪乱の 影響をどのように受けているかについて調べている。 霊長類のみを対象にした調査では,調査域における 対象種の存在をカメラトラップで確認した研究 (Easton et al, 2011)や,確認した結果に基づいて既存の分布域 の改訂を提案している研究 (Lhota et al, 2012;Martins et al, 2017)がある。映像はその種が存在することの強い 証拠となるため,地元住民などによってのみ確認され ていた稀な種の存在を確定したい場合などに,カメラ トラップは強力な武器になるだろう。ただし,狙った 種が撮影されるかどうかはカメラの設置場所や設置期 間,その種の生態の影響を大きく受ける。種多様性の 高い熱帯で稀な種も含めた哺乳類リストを完成させる ためには,数千日以上の合計カメラ稼働時間が必要で あると考えられている (Rovero et al, 2013) (Karanth, 1995 Burton, 2012;Hanekom & Randall, 2015;Nakashima et al, 2013;Zhang et al, 2017) ,そして占有率を推定した論文が 2 本 (Bowler et al, 2017Brodie & Giordano, 2013) De Moraes et al, 2014;Estienne et al, 2017;Lapuente et al, 2017;Luncz et al, 2017;Torralvo et al, 2017b) Olson et al, 2012;Tan et al, 2013) (Hofmeester et al, 2017;Rowcliffe et al, 2011) 。 あるいは,よりシンプルにどのような条件でも撮影確 率が 100%になる範囲をあらかじめ確かめ (Nakashima et al, 2018 (Engelbrecht, 2016;Olson et al, 2012;Wolovich et al, 2017) ラを用いて色彩や形態を分析した研究が数多くある霊 長類学において,これは意外な事実である (Caillaud e...…”
unclassified